Utilising A Silastic Sheet In Endoscopic Sinus Surgery To Prevent The Formation Of Lateral Synechiae - Ali, Muhammad; Malik, Farhat Jabeen; Arif, Nighat (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the formation of lateral nasal synechiae after endoscopic sinus surgery with and without insertion of a silastic sheet between the middle turbinate and lateral nasal wall. Methods: This study includes 70 patients of either gender, 20-60 years of age, admitted for elective endoscopic sinus surgery for chronic rhinosinusitis. Patients were divided into two groups. In group S, a silicone sheet was placed between the middle turbinate and the lateral nasal wall. While in group-T, no silicone sheet was placed. All patients were evaluated for the development of lateral nasal synechiae up to the 6th post-operative month. Results: In group-S, 3 (8.6%) patients developed lateral nasal synechiae, while in group-T, 11 (31.4%) patients developed lateral nasal synechiae. Comparison of both groups showed a p-value of 0.017. Conclusion: Silastic sheet placement in the middle meatus significantly reduces the formation of lateral nasal synechiae after endoscopic sinus surgery.